Pengaruh Harga, Citra Merek dan Kepercayaan Merek Terhadap Loyalitas Merek (Studi Kasus Pada Pengguna SmartPhone Realme di Kota Probolinggo) - Riski Bagus Satria; Rois Arifin; Siti Asiyah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This research was conducted to see the effect of price, brand image and brand trust on consumer loyalty for Realme Smartphone products in the city of probolinggo.The type of research used this time is explanatory research, with population of 152 consumer data obtained from Realme outlets throughout the city of Probolinggo. The technique used in sampling is probability sampling, with the number of respondents obtained as many as 110 people.The results of thie research indicate there is a significant positive effect carried out by the variables of price, brand image, and brand trust on consumer loyalty of the Realme smartphone products.  Keywords: Loyalty, Price, Brand Image, Brand Trust